Populations de langue officielle en situation minoritaire selon différentes méthodes de dénombrement. Rapport - Guignard Noël, Josée; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2020)

Health Data for Linguistic Minority Group Research in Canada: Proof-of-Concept Centralized Health Care Metadata Repository Development and Usability Study - Martin-Schreiber, Vincent; Peixoto, Cayden; Batista, Ricardo; Belanger, Christopher; Tanuseputro, Peter; Hsu, Amy T; Bjerre, Lise M (JMIR Infodemiology, 2026)
Background Language barriers between Canadian patients and health care providers are associated with poorer health outcomes, including decreased patient safety and quality of care, misdiagnosis and longer treatment initiation times, and increased mortality. However, research exploring language as a social determinant of health is limited, as Canadian health data are scattered across many jurisdictions, each with its own policies and procedures. This fragmentation makes it difficult for researchers to identify, locate, and use existing data. This paper presents the results of a pilot study that attempts to address this gap by creating a metadata repository (MDR) to act as a central source of information about what data are available at which data holdings across Canada. Objective This project aimed to (1) create a proof-of-concept MDR for Canadian health data at the variable level; (2) identify and label language-related variables existing within the MDR data; and (3) develop an interactive, public-facing web application to let users browse and search the MDR. Methods Metadata were collected from 5 Canadian health data sources, including 4 provincial data holdings and 1 national survey, and pooled to create a data repository. Then, we performed bottom-up labeling of language-related variables within the pooled metadata by first using a search string algorithm across all variable labels, names, and definitions and then consensus screening these variables using a derived, standardized definition of language or linguistic variables. Using the Shiny web framework in R, we then developed an openly accessible web application to allow users to search the proof-of-concept MDR. Results A total of 850,343 variables were collected and included in the repository, with most coming from Ontario (n=712,037, 83.7%) and Manitoba (n=97,051, 11.4%) provincial data holdings. Among all variables in the repository, 213,696 (25.1%) were confirmed to be language related. Conclusions Developing a national MDR would be a transformative opportunity for Canadian researchers to leverage the full scope of Canadian health administrative data. Although a top-down approach with consistent engagement of and collaboration between provincial data holdings and federal data agencies is ideal to develop a national MDR, this study demonstrates the feasibility of a bottom-up approach in contributing to this overarching goal.

Access to health and social services for Quebec’s English-Speaking Minority Communities: Recent challenges, legislative context, and research recommendations. - Shoumarova, Lina (Quebec English-Speaking Communities Research Network, 2024)

Accès aux soins de santé pour les communautés québécoises d’expression anglaise – Principaux enjeux et besoins en matière de recherche - Shoumarova, Lina; Pocock, Joanne; Donovan, Patrick; O'Donnell, Lorraine (Université Concordia, 2025)
Le présent document résume les travaux de recherche qui ont été menés récemment sur l’accès aux services de santé et aux services sociaux pour la communauté de langue officielle en situation minoritaire (CLOSM) anglophone du Québec. S’appuyant sur la Bibliographie sur le Québec anglophone, la Bibliothèque ouverte du savoir communautaire et le centre de documentation du Réseau communautaire de santé et de services sociaux (CHSSN), il met en lumière les principaux thèmes traités, les lacunes dans la recherche et les domaines où d’autres travaux de recherche doivent être menés en priorité.